2016
DOI: 10.1002/joc.4964
|View full text |Cite
|
Sign up to set email alerts
|

Spatial downscaling of TRMM‐based precipitation data using vegetative response in Xinjiang, China

Abstract: Station-based observed precipitation data are available in a limited way and only at low spatial resolution. High-resolution satellite rainfall products can help to monitor precipitation changes over large areas. The Tropical Rainfall Measuring Mission 3B43 (TRMM 3B43) precipitation data with coarse spatial resolution and low data accuracy are capable of depicting the spatial variability of precipitation, but fail to estimate the accurate magnitude. These data available in Xinjiang, China, need to be evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…The GDA and GRA methods have proven to be simple and effective methods to correct the errors in the downscaled data [41,74,75]. In this study, calibration using GDA and GRA methods gave better annual precipitation in terms of statistical indicators for the three reference years and the entire time period.…”
Section: Sources Of Errors and Limitations In The Downscaled Satellitmentioning
confidence: 69%
“…The GDA and GRA methods have proven to be simple and effective methods to correct the errors in the downscaled data [41,74,75]. In this study, calibration using GDA and GRA methods gave better annual precipitation in terms of statistical indicators for the three reference years and the entire time period.…”
Section: Sources Of Errors and Limitations In The Downscaled Satellitmentioning
confidence: 69%
“…Jia et al [14] introduced both NDVI and Digital Elevation Model (DEM) as the explanatory variables in a Multiple Linear Regression (MLR) model. Independent station validation in the two studies and later studies [15,22,24,30] showed that the downscaled precipitation based on ER or MLR after residual correction was comparable with the original TRMM product but at much improved resolution.…”
Section: Advances In Meteorologymentioning
confidence: 84%
“…Therefore, it is a feasible approach to downscale precipitation through establishing statistical models of precipitation and these factors, and this is termed as statistical downscaling algorithms. Their fundamental statistical theories could be classified into regression analysis [14,15,[22][23][24] and machine learning methods such as Artificial Neural Network [25,26] and random forests [27][28][29].…”
Section: Advances In Meteorologymentioning
confidence: 99%
“…In order to provide an appropriate application guidance of the satellite‐based precipitation products in different regions (Li et al, ), both evaluation and validation of the accuracy and applicability of satellite‐based precipitation products over different regions around the world have become a necessary requirement. During past decades, numerous relevant studies have been carried out at national or basin scale in different regions (Behrangi et al, ; Diem et al, ; Kumar et al, ; Li, Zhang, & Xu, ; Liu, Chen, Lian, & Lou, ; Prakash et al, ; Ricardo et al, ; Su et al, ; Tekeli et al, ; Worqlul et al, ; Xue et al, ; Zhao & Yatagai, ), including in China such as the Tibetan Plateau (Meng et al, ; Tong et al, ; Zeng, Li, & Li, ), the north‐west China (Yang & Luo, ; Zhang et al, ), south‐west China (Liu et al, ), north‐east China (Yong et al, , ), and south China (Jiang et al, ; Hu, Yang, Wang, & Yang, ; Hu, Yang, Wang, Yang, & Liu, ; Li et al, , ; Tang et al, ; Yong et al, ). In these studies, the in situ observation‐based comparisons were widely used as the method of evaluation.…”
Section: Introductionmentioning
confidence: 99%